Quality of Environmental Sustainability Reporting in Container Shipping - ÇIKIKCI, Alperen; SİGALI, Seçil (International Journal of Contemporary Economics and Administrative Sciences, 2025)
The quality of sustainability reporting (QSR) has become a focal point for both scholars and practitioners, largely due to heightened concerns surrounding corporate transparency and the risk of “greenwashing.” QSR comprises dimensions such as materiality, credibility, completeness, and assurance, ensuring that disclosed information is both relevant and reliable. This study investigates QSR dimensions in the container shipping industry, emphasizing the disclosure of environmental materiality and the extent to which external assurance is employed. Through conceptual content analysis of 47 sustainability reports published between 2018 and 2022 by the world’s top ten container shipping companies, the findings indicate that, although firms dedicate considerable attention to emissions and energy consumption, other issues (e.g., biodiversity, effluents) are comparatively underrepresented. Moreover, only a subset of these environmental disclosures undergoes external assurance, and the analysis focuses on the presence of assurance rather than the specific scope or type of engagements, which further calls into question the overall reliability and comprehensiveness of the reported information. The results highlight the need for more robust and standardized assurance frameworks and for closer scrutiny of QSR to enhance stakeholder confidence in container shipping’s sustainability reporting.